Volumetric and Ultrasonic Properties of Liquid Mixtures of Ethyl Benzene with Alkanols at Different Temperatures - Sanaullah, A. F. M.; Uddin, M. A. (Journal of Scientific Research, 2024)
The densities (ρ), and ultrasonic speeds (u) of pure ethyl benzene, 1-butanol, 1- pentanol, and those of their binary mixtures, with ethyl benzene as a common component, covering the whole composition range have been measured at 298.15, 303.15, 308.15, 313.15, 318.15 and 323.15 K. From the experimental data the excess molar volume (VmΕ), deviations in isentropic compressibility (∆κs) and deviations in ultrasonic speed (∆u) have been determined. The sign and magnitude of these parameters were found to be sensitive towards interactions prevailing in the studied systems. The excess or deviation properties (VmΕ, Du, or ∆κs) have been correlated using a Redlich-Kister type equation to obtain their coefficients and standard deviations. The variations of derived parameters mentioned above with composition offer a convenient method to study the nature and extent of interactions between the component molecules of the liquid mixtures, which are not easily obtained by other means.